Policy for Drug Users in Indonesia: A Critical Policy Analysis of Jail Punishment and an Alternate Rehabilitation Policy - I Nyoman Sutarsa (Universitas Udayana, 2014)
Given the fact that drug use is a complex problem, public intervention to change and address its determinants are crucial. Social and economic capitals should be channelled via several options, ranging from ‘pro to the poor’ policy, micro economic enterprise, diversion from informal economy, community engagement, social health insurance for poor people, economic development strategy for community and national level and employment initiatives or providing wider access for job opportunity. National public health policy strategies regarding drug user treatment are also necessary to facilitate future interventions.